Infant Oral Healthcare and Anticipatory Guidance Practices among Dentists in a Pediatric Care Shortage Area - Eman A. Bakhurji; Hassan M. Al-Saif; Mohammed A. Al-Shehri; Khalid M. Al-Ghamdi; Mohamed M. Hassan (International Journal of Dentistry)
Objectives. To assess dentists’ practices and barriers towards infant oral healthcare (IOH) and anticipatory guidance (AG) in eastern Saudi Arabia. Methods. A regional, cross-sectional survey was distributed to 340 (323 general dentists (GPs) and 17 pediatric dentists (PDs)) working in a governmental setting in eastern Saudi Arabia. A 23 close-ended, pilot-tested questionnaire was developed. The questionnaire asked about dentists’ IOH and AG practices. A five-point Likert scale question assessed barriers interfering with AG practices. Descriptive and multivariate logistic regressions were used. Results. Participation rate was 98.5% (335/340). Only 18% of GPs indicated performing IOH exams, while 100% of PDs do. About 90% of GPs would see children on a first visit when they are ≥3 years old, whereas 60% of PDs reported seeing one-year-old children. Older practitioners and those performing AG were more likely to perform IOH (OR = 1.8, CI = 1.06–3.1, and OR = 3.84, CI = 1.93–7.65, resp.). The majority of respondents (94%) felt their training did not prepare them to practice AG. “Parents bringing their children for the first time for emergency or existing conditions” was cited by 99% of respondents as a barrier to performing AG. Conclusion. Increasing the awareness of GPs and parents about the importance of IOH and AG is crucial in improving children’s oral health. Collaboration with pediatricians for early referral of children is equally important in increasing the awareness on prevention principles.